PENERAPAN STANDAR OPERASIONAL (SOP) DALAM PENGELOLAAN BARANG MILIK NEGARA (BMN) DI KANTOR BNN PROVINSI SUMATERA UTARA - Nasution, Ahmad Zidan; Hasibuan, Nur Fadhilah Ahmad (LP2M Universitas Bina Bangsa, 2025)
The aim of this research is to illuminate how effective the implementation of Standard Operating Procedures (SOP) is in the management of State Property (BMN) at the North Sumatra Province BNN Office, management must comply with national assets and not conflict with applicable laws and regulations. Qualitative descriptive research collects data through documentation and interviews. Research shows that Standard Operating Procedures (SOPs) have been created and announced, but there are several challenges, especially related to employee understanding and compliance with existing SOPs. Only around 60% of employees understand and implement SOPs, which shows that there is a gap between established policies and practice in the field. The lack of training and outreach from BNN management is the main factor hindering this understanding, so more intensive efforts are needed to increase employee knowledge and skills in managing BMN